2018
DOI: 10.1007/s12291-018-0735-0
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Attenuates ELMO-1 and KIM-1 Expression and Oxidative Stress in the Kidney of Rats with Type 2 Diabetes

Abstract: Chronic diabetes mellitus is accompanied with overexpression of ELMO1 and KIM1 and enhanced oxidative stress. This study was aimed to evaluate the effects of administration of silymarin on oxidative stress markers and ELMO1 and KIM1 expression in the kidney tissue of type 2 diabetic rats. In this experimental study, 36 male Wistar rats were divided into 6 groups: Control, silymarin-treated control (60 and 120 mg/kg/day), diabetic, and silymarin-treated diabetic groups (60 and 120 mg/ kg/day). Tissue levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Results; the increase in ROS levels increased tissue lipid peroxidation (TBARS) and decreased antioxidant activity (GSH) (de Avelar et al, 2017;Heidari et al, 2018;Placer et al, 1966). According to the hypothesis announced by the researchers, SLY reduces lipid peroxidation due to its antioxidant properties and increases endogenous concentrations of antioxidant enzymes such as GSH, thereby reducing nephropathy by preventing cellular damage (Goli et al, 2019;Zheng et al, 2014). In addition, SLY sweeps up the free radicals and prevents lipid peroxidation, thereby reducing the damage to the cells and fixing the cell membrane (Shereen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results; the increase in ROS levels increased tissue lipid peroxidation (TBARS) and decreased antioxidant activity (GSH) (de Avelar et al, 2017;Heidari et al, 2018;Placer et al, 1966). According to the hypothesis announced by the researchers, SLY reduces lipid peroxidation due to its antioxidant properties and increases endogenous concentrations of antioxidant enzymes such as GSH, thereby reducing nephropathy by preventing cellular damage (Goli et al, 2019;Zheng et al, 2014). In addition, SLY sweeps up the free radicals and prevents lipid peroxidation, thereby reducing the damage to the cells and fixing the cell membrane (Shereen et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It can directly damage cellular molecules such as proteins, lipids and DNA, and alter signal paths through the activation of redox-sensitive transcription factors. VPA treatment has been associated with oxidative stress in a number of studies in both human and animal models, particularly in the kidneys, causing serious damage to cells, necrosis and atrophy (Emekli-Alturfan et al, 2015;Goli et al, 2019;Heidari et al, 2018). VPA causes renal ROS, depletes glutathione (GSH) reservoirs, reduces tissue antioxidant capacity; thiobarbitüric acid reactive substance (TBARS) and other lipid peroxidation products increase the amount (Heidari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenate was resuspended in ice cold lysis buffer (10mM HEPES, 10mM KCl, 1.5mM MgCl2, 1mM EDTA, 0.2% triton X100, 0.5mM dithiothreitol, protease inhibitor cocktail, pH 7.9) and incubated on ice for 20min. The tissue homogenates were vortexes and centrifuged (14,000g; 10min; 4°C), and the supernatants were retained for analysis (Goli et al, 2019).…”
Section: Tissue Collection and Processingmentioning
confidence: 99%
“…Recently recognized that apoptosis, neuron degeneration and oxidative stress are significantly raised in the hippocampus of animal models of DM (Seto et al, 2015). The oxidative stress imposed by reactive oxygen species plays an important role in many chronic and degenerative diseases (Ardjmand et al, 2019;Goli et al, 2019). Studies suggested that antidiabetic drugs could offer therapeutic benefits to DM-related impairment of cognitive functioning in both patients and animal models (Risner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%